Controlled synthesis of bimetallic Pd–Rh nanoframes and nanoboxes with high catalytic performances. Issue 21 (7th May 2015) - Ye, Wei; Kou, Shufang; Guo, Xia; Xie, Fang; Sun, Hongyan; Lu, Haotian; Yang, Jian
Abstract : Bimetallic nanoframes and nanoboxes of Pd–Rh are synthesized by selective removal of Pd cores from different Pd–Rh nanocubes prepared by a hydrothermal reaction of PdCl2, RhCl3 and HCHO. Abstract : Bimetallic nanoframes and nanoboxes of Pd–Rh are synthesized by selective removal of Pd cores from different Pd–Rh nanocubes prepared by a hydrothermal reaction of PdCl2, RhCl3 and HCHO. HCHO in the procedure alters the reaction kinetics and the growth behavior of Pd and Rh, resulting in different nanocubes that determine the following hollow nanostructures, nanoframes or nanoboxes. The catalytic properties of the hollow nanostructures are investigated using the oxidation of o -phenylenediamine (OPDA) to 2, 3-diaminophenazine (DAP) as a model reaction. The resulting bimetallic nanoframes and nanoboxes show enhanced conversion efficiencies compared to their solid counterparts. This method offers a convenient way for mass production of bimetallic hollow nanomaterials.